Barriers to effective employability skills training programs - Mohd Puad, Mohd Hazwan (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Employability skills training programs are an essential strategy to improve the skills of the workforce and minimize unemployment in Malaysia. However, there has been a lack of assessment and evaluation studies regarding local employability skills training programs. Existing local studies are focused more on the identification of the skills that allow a person to be employable. Due to the lack of assessment and evaluation studies, stakeholders seem perplexed about the direction of training programs. Therefore, the purpose of this study was to examine the perceptions of educators, employers, and recent graduates regarding the barriers that impede the progress of employability skills training programs. The theoretical framework for this descriptive study was based on Human Capital Theory (Becker, 1993; Schultz, 1961). All participants for this study were from the central economic region of the west coast of peninsular Malaysia. The findings of this study revealed the major barriers to effective employability skills training programs in the workforce of Malaysia, such as unclear objectives and direction of training programs, negative attitudes of recent graduates, and employers not actively involved in workforce education and training.